BERAKHIRNYA PERJANJIAN PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA - Zumrotul Wahidah (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTAgreement is a law relationship which one binds one or more people that cause law consequence. The agreement would be carried out in accordance and it is appropriate by contract that was agreed upon Islamic law or civil law. Agreement of Islamic law are called sharia agreement that implementation systems embrace sharia principle. While agreements of civil law are called conventional agreement that the implementation systems embrace civil law. Every agreement would be raised the rights and obligation of each parties. If the agreement have been fulfiilled or not that caused by deviations. It results bot Islamic or civil law become extinct, it is appropriate with the agreement made by the parties. There is a difference at the end of the agreement in sharia and conventional, it provides a concept for interpreneurs in the field of economics at the sharia or conventional financial institutions which have developed rapidly at this time.Key Words: The End Of Agreement, Islamic Law, Civil Law.